Evaluation of hot water and microwave blanching on qualities and sensory characteristics of water dropwort (Oenanthe javanica DC.). Issue 10 (5th July 2019) - Tang, Mingming; Sun, Hanju; Zhang, Zuoyong; Zhao, Jinlong; Cao, Juanjuan; Thakur, Kiran; He, Shudong
Abstract: In the present study, water dropwort was comparatively treated in hot water blanching (HWB) and microwave blanching (MWB). The changes in polyphenol oxidase (PPO), weight loss, phytochemicals, color, firmness, flavor, and sensory evaluation were investigated. The sensory preference was predicted via artificial neural network (ANN) model. Results showed that high heating intensity inactivated PPO activity, enhanced lightness and greenness, but caused damage to the texture both in HWB and MWB. Moreover, MWB yielded lower weight loss and retained higher contents of ascorbic acid, soluble proteins, sugars, flavonoids, and total polyphenols than HWB. However, E‐nose and E‐tongue analysis indicated that HWB was more conducive for reducing undesired flavor. Importantly, ANN model suggested that the color and taste were the remarkable factors influencing sensory preference. Overall, blanching at 600 W for 1 min was predicted as the preferable condition for meeting sensory acceptability, and MWB could be a good alternative to HWB. Practical applications: Blanching is usually considered as a suitable pretreatment to inactivate enzymes of the fruits and vegetables. Microwave blanching has gained significant momentum due to its capability of providing rapid and volumetric heating. The results of this study provide substantial information for comparing the effects of HWB and MWB on the qualities and sensory properties of water dropwort. Moreover, highlighting sensory analysis might be of importance to obtain insight into consumer attitudes toward products. Furthermore, artificial neural network model is served for comparing the influence of HWB and MWB on the sensory preference, which would be more valuable to control the food quality and satisfy the sensory requirements in actual production.